Effect of Arsenic Stress on Expression Pattern of a Rice Specific miR156j at Various Developmental Stages and Their Allied Co-expression Target Networks - Pandey, Akhilesh Kumar; Gedda, Mallikarjuna Rao; Verma, Ashok K. (Frontiers in Plant Science, 2020)
IIn plants, arsenic (As) stress modulates metabolic cascades at various developmental stages by influencing the pattern of gene expressions mediated by small non-coding RNAs, especially Micro-RNAs, involved in the moderation of a myriad of cellular processes needed for plant adaptation upon oxidative stress. miR156j of miR156 gene family, involved mainly in the regulation of growth and development in plants. This study was designed to find out the role of arsenic toxicity on Osa-miR156j expression in all physiological growth stages. To better understand the functional role of Osa-miR156j in rice, we observed the expression in different developmental stages (seedlings, tillering & flowering) and various tissues of leaf, stem and root tissues (at 0, 24, 48 & 72 hours) under 25 µM arsenite (As (III)) exposure. Additionally, using bioinformatic tools to target genes of Osa-miR156j and the potential co-expressed genes were explored at different development stages in the various tissues of rice under stress conditions. The expression of Osa-miR156j showed its temporal downregulation in various tissues in different developmental stages. Of note, the downregulation was more pronounced in root tissues at seedlings, tillering, and flowering stages during 0-72 hours under arsenite exposure as compared to other tissues. Overall, the As stress altered the gene expression more prominently at seedlings developmental stage followed by flowering and tillering. Additionally, through the In silico approach, the target functions and presence of oxidative stress-responsive cis-acting regulatory elements/motifs also confirmed Osa-miR156j involvement in the regulation of arsenic stress in rice. The findings of this study demonstrate the prominent role of Osa-miR156j in rice under arsenite stress, which was found to modulate the metabolic activities in rice plants at different developmental stages, and thus it might be useful for the development of arsenic tolerant varieties.